2015
DOI: 10.1148/radiol.14131164
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma: Stiffness Value and Ratio to Discriminate Malignant from Benign Focal Liver Lesions

Abstract: Use of stiffness values measured in the liver parenchyma at more than 2 cm from the lesion allowed better diagnostic performance than did values measured in a region closer to the tumor. Stiffness value was more accurate than stiffness ratio for differentiation of malignant from benign focal liver lesions, but the stiffness ratio might be useful for subclassification of benign and malignant lesions. Online supplemental material is available for this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 21 publications
4
36
0
Order By: Relevance
“…[17] Since carcinomas were found to be stiffer than adjacent normal tissues and studies reported that histologically different tumors may display different elasticity patterns according to tissue architecture, [7,10] this technique has been successfully applied to differentiate focal lesions of testis, breast, prostate, pancreas and liver. [14,[18][19][20] Recently, shear wave elastography (SWE) which combines B-mode image with color-coded US generating a quantitative image SWE (kPa) of the tissue stiffness started to be used to exhibit different hardness among different tissue regions in real-time conditions. [21] With the use of SWE, different elasticity values dependent on testicular volume and functional properties have been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Since carcinomas were found to be stiffer than adjacent normal tissues and studies reported that histologically different tumors may display different elasticity patterns according to tissue architecture, [7,10] this technique has been successfully applied to differentiate focal lesions of testis, breast, prostate, pancreas and liver. [14,[18][19][20] Recently, shear wave elastography (SWE) which combines B-mode image with color-coded US generating a quantitative image SWE (kPa) of the tissue stiffness started to be used to exhibit different hardness among different tissue regions in real-time conditions. [21] With the use of SWE, different elasticity values dependent on testicular volume and functional properties have been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Study characteristics All 9 papers [13,[16][17][18][19][20][21][22][23] were prospective diagnostic cohort studies. A total of 1046 FLLs from 968 patients were identified, 679 (64.9%) lesions being malignant.…”
Section: Resultsmentioning
confidence: 99%
“…The items of flow and timing were of low quality. Three studies performed histology for final confirmation using fine needle aspiration cytology [17], targeted biopsies of lesions [21], and surgical specimens [23]. Other studies [13,16,[18][19][20]22] (fig 3).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the patient with multiple FLL, only the largest or the most conspicuous one on ultrasound was chosen. Ten additional ElastPQ measurements were performed in the normal surrounding liver parenchyma at least 2 cm from the lesion [24], over the same ultrasound scanning section and on the same depth of the focal liver lesions. The ratios of the elasticity of the lesions to the surrounding liver were determined.…”
Section: Elastpq Measurementsmentioning
confidence: 99%